UJI SITOTOKSIK EKSTRAK ETANOL 50% DAUN KITOLOD (Isotoma longiflora (L.) Presl.) TERHADAP SEL KANKER SERVIKS (Ca Ski Cell Line) SECARA IN- VITRO - yanti, Aprilita rina (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
Kitolod (Isotoma longiflora (L.) Presl.) Is a traditional medicinal plant which is efficacious as anticancer. Empirically kitolod had been used by Indonesian people for the treatment of cancer, but this remains to be proven scientifically through research. The objective of this research was to determine the cytotoxic activity of 50% Ethanol Extract of Kitolod leaves (Isotoma longiflora (L.) Presl) at a concentration of 25 mg / mL, 50 mg / mL, 75 mg / mL, and 125 mg / mL against cervical cancer cells (Ca Ski Cell Line) in vitro assay using red natural methods.Results of Cytotoxic assay shows that IC50 values 50% Ethanol Extract of Kitolod leaves (Isotoma longiflora (L.) Presl) in Ca Ski Cell Line is 55.78 ug / mL. Ethanol extract at concentration of 25 mg / mL, 50 mg / mL, 75 mg / mL, and 125 mg / mL have cytotoxic effecst against cervical cancer cells (Ca Ski Cell Line) and extract at a concentration of 125 ug / mL indicates the largest percentage of cell death.